Morphological identification of the soft coral, Clavularia inflata, reveals different sclerite characters across Indonesian coral reefs - Beginer Subhan; Dietriech G Bengen; Sebastian Ferse; Fauzan Dzulfannazhir; Nurlita Putri Anggraini; Prakas Santoso; Dondy Arafat; Lalu M. Iqbal Sani; Prehadi Prehadi; Hawis Madduppa (Depik, 2022)
Soft corals of the genus Clavularia (Blainville 1830) have complex and difficult to distinguish morphological characteristics, making them rather difficult to identify. A paucity of information exists for Indonesian coral reefs, a complex biogeographic region at the confluence of the Pacific and Indian Ocean that covers an extensive geographic area and several marine ecoregions, is subject to several ocean current systems, and includes a high diversity of habitats. Specimens of Clavularia inflata were collected from eleven study sites across the Indonesian archipelago, morphologically described based on their sclerite characteristics, and compared among sites. Sclerite observations were divided into four parts for each colony, namely pinnules, crowns, calyces, and stolons. The sclerites found in C. inflata comprised various forms such as rods, fingers, sticks, and brackets. Morphometric measurements of C. inflata showed specimens from Kepulauan Seribu had the largest pinnule, calyx, and stolon sclerites compared to other locations. The maximum mean size of crown sclerites was observed for specimens from Maluku Tenggara Barat. Similarities in the shape of sclerites resulted in specimens from Kangean, Morotai, Tanjung Lesung, Bontang, Lombok and Natuna forming a cluster, while those from Maluku Tenggara Barat and Arborek were dissimilar to other sites. Smaller sclerite sizes in specimens from Arborek are likely related to strong currents at that site. In conclusion, there were variations in the size of sclerites across the eleven study sites, with several sites forming a cluster of similar sclerite dimensions. Further studies using molecular markers are suggested to further explore the possibility of cryptic species.